Assessing the impact of the reactivity of red brocket deer (Mazama americana) on training efficiency - Lara Caveanha Gragnanello; Mariana Parra Cerezo; Cristiane Schilbach Pizzutto; Mateus José Rodrigues Paranhos da Costa (PLoS ONE, 2025)
The reactivity of wild animals has been studied due to its influence on ex-situ management and conservation strategies. However, there is insufficient research examining the impact of reactivity on training processes for veterinary handling procedures, which are essential for promoting the welfare of wild animals in conservation centers, zoos, and research institutions. This study aimed to evaluate the influence of reactivity on training for veterinary procedures in red brocket deer (Mazama americana). The reactivity of twelve red brocket deer were measured by recording their behavior in the presence of an unfamiliar person and during routine handling procedures. Subsequently, the deer were subjected to habituation and operant conditioning (employing positive reinforcement) for veterinary handling procedures. There were individual differences in the habituation process. Nine deer, which voluntarily approached the unknown person and showed calmness during handling procedures, progressed to the second phase of the study. The remaining three stayed in the habituation stage throughout the study and exhibited positive values in dimension one of Multiple Correspondence Analysis (MCA), indicating that they required more habituation sessions. Only five deer that participated in operant conditioning learned all the proposed commands, with four demonstrating very low reactivity in the behavioral tests. The overall success rate was 41.66%, indicating that only five of the twelve deer completed the learning process. We concluded that the most reactive deer, characterized as restless and agitated, performed poorly in habituation and operant conditioning, while less reactive deer, which were calmer and exhibited minimal movement, learned more commands. This study provides insights that can contribute to developing management strategies for cervids, facilitating the implementation of more personalized training approaches, and promoting animal welfare and handlers’ safety.